2005
DOI: 10.1007/s11199-005-1197-4
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity, Femininity, and the Bem Sex Role Inventory in Turkey

Abstract: The aim of this study was to examine the masculinity and femininity scales of Bem Sex Role Inventory (BSRI) among Turkish university students. Five hundred thirty-six students (280 men and 256 women) volunteered to complete the short-form of the BSRI and answer demographic questions. In factor analyses, the original factor structure (Bem, 1981) was found both in the men's and women's data. Comparisons of the factor structures with target rotation (Procrustes rotation) and comparison indexes showed no differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 22 publications
(22 reference statements)
3
74
0
2
Order By: Relevance
“…These characterizations are consistent across various cultures, time spans and diverse employment settings (Auster and Ohm, 2000;Schein, 2001;Ozkan and Lajunen, 2005;Rudman et al, 2008;Heilman, 2012;Xiumei et al, 2012). Laboratory studies have shown that women award themselves lower wages, are less likely to demand equivalent wages and are more satisfied to receive lower earnings than their male counterparts (Honeyman and Goodman, 1991;Wajcman, 2000;Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These characterizations are consistent across various cultures, time spans and diverse employment settings (Auster and Ohm, 2000;Schein, 2001;Ozkan and Lajunen, 2005;Rudman et al, 2008;Heilman, 2012;Xiumei et al, 2012). Laboratory studies have shown that women award themselves lower wages, are less likely to demand equivalent wages and are more satisfied to receive lower earnings than their male counterparts (Honeyman and Goodman, 1991;Wajcman, 2000;Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 73%
“…In the other half of the paired applications, women were self-characterized as being gentle, friendly and affectionate; reflecting the so-called 'women with feminine personality characteristics' group (Bem, 1981). Scientists have used the Bem Sex Role Inventory (Bem, 1981) to provide a measure of gender-role stereotyping (Archer and Lloyd, 2002;Ozkan and Lajunen, 2005;Calvo-Salguero et al, 2008). In the latter inventory, gender stereotypes refer to the beliefs people hold in relation to members categorized as 'man' or 'woman' (Archer and Lloyd, 2002 Zinc, 2013).…”
Section: Design Of the Experimentsmentioning
confidence: 99%
“…Finally, feminine traits are those that are evaluated to be more suitable for women than men (for example, being gentle and cheerful). Recent attempts to validate the contents of the Bem Sex-Role Inventory have provided evidence for the persistence of these stereotypes across different countries (Ozkan and Lajunen, 2005;Xiumei et al, 2012). Importantly, to ensure that any differences in treatment could be attributed to sexual orientation bias, I matched CVs that mentioned gay and lesbian university union membership with CVs that mentioned human rights union membership (see Tilcsik, 2011).…”
Section: Sexual Orientation Labellingmentioning
confidence: 99%
“…As it is well known, masculine traits are attributed to males, whereas feminine traits are attributed to females (Özkan & Lajunen, 2005;Peplau, Hill, & Rubin, 1993;Winstead & Derlega, 1993). Competitiveness, independence, dominance are some examples of the masculine traits and empathy, nurturance, and being sensitive to the needs of others are some examples of feminine traits (Basow, 1992).…”
Section: Sex Role Orientationmentioning
confidence: 99%